Jaringan Korupsi Dinas Kehutanan Riau Pada Putusan Mahkamah Agung Nomor 22/Tipkor/2015/Pt. Bdg: Riau Forestry Service Corruption Network on Supreme Court Verdict Number 22/Tipkor/2015/Pt. Bdg - A. Andika Yasa (JOURNAL OF GOVERNMENT SCIENCE, 2021)
Hand Arrest Operations carried out by the Indonesian Corruption Eradication Commission (KPK) to Governor of Riau Province, Annas Maamun, drew much attention. The case originated from the conversion of some parts of protected forest to become a non-forest area in Indragiri Hulu District. This research attempts to understand the involvement of various actors in the corruption case of the Governor through Forestry Service of Riau Province; and secondly, to understand corruption networks within the Forestry Service based on Supreme Court verdict No. 22/TIPIKOR/2015/PT.BDG. The findings show that the actors in the corruption case involved Annas Maamun as Governor, Zulkifli Hasan as Minister of Forestry 2019-2004, and other government institutions in the Riau Province. From corporations, Manurung and Edison Siahaan had been involved as company owners who urged the Governor to facilitate forest conversion. From a presumed independent actor’s side, Koran Riau (a newspaper) played role to minimize or “neutralize” news on such corruption case. In addition, interaction among the actors had a certain pattern, with the modus operandi of the corruption having included gratification, bribery, fraud, and abuse of power.